2012
DOI: 10.12659/msm.883637
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically-assisted reduction and fixation of an old osteochondral fracture of the lateral femoral condyle

Abstract: SummaryBackgroundOsteochondral fracture (OCF) of the lateral femoral condyle has a low incidence and old OCF is even more rarely seen; it is difficult to differentiate from late osteochondritis dissecans (OCD).Case ReportIn this report, we present the case of a 20-year-old male patient with an old OCF of the lateral femoral condyle. The possible etiology of OCF is discussed, along with its clinical manifestation, diagnosis, and treatment. He underwent arthroscopically-assisted reduction and fixation with cannu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…However, one of these studies was reported on the lateral femoral condyle and the other on the patella, which is different from our case. One of these studies is about arthroscopy-assisted osteochondral fracture fixation in a male patient aged 20 who had pain in the left knee for six months without history of trauma 10 , whereas the other study is about fixation of a patellar osteochondral fracture at week 8 after trauma in a female patient aged 23 11 . This indicates that osteochondral fracture fixation, even if it is delayed, leads to successful clinical outcomes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…However, one of these studies was reported on the lateral femoral condyle and the other on the patella, which is different from our case. One of these studies is about arthroscopy-assisted osteochondral fracture fixation in a male patient aged 20 who had pain in the left knee for six months without history of trauma 10 , whereas the other study is about fixation of a patellar osteochondral fracture at week 8 after trauma in a female patient aged 23 11 . This indicates that osteochondral fracture fixation, even if it is delayed, leads to successful clinical outcomes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In this study, we present a rare case of a penetrating knee injury in a pediatric patient involving an osteochondral fragment from the lateral femoral condyle. Osteochondral fractures of the lateral condyle of the femur are rare but can frequently cause significant knee joint pain and joint degeneration [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteochondral fracture of the lateral femoral condyle is a rare injury of the knee joint, which mostly occurs in adolescence. In adolescence, the cartilage‐bone interface is the weakest transitional area in the knee joint, and there is no obvious boundary between calcified and uncalcified cartilage.…”
Section: Introductionmentioning
confidence: 99%